Tingkat Pengetahuan Ibu tentang Stimulasi Perkembangan Berhubungan dengan Berkembangan Balita - Pariyem Pariyem; Siti Maimunah; Ulfa Tantriyanna (Malahayati Nursing Journal, 2023)
ABSTRACT Good knowledge of mothers about developmental stimulation will affect the development of toddlers. Mothers have good knowledge of developmental stimulation, so their toddlers will have appropriate and optimal development. To analyze the relationship between the mother's level of knowledge about developmental stimulation and the development of toddlers at the jasmine posyandu, Gendingan Village, Ngawi Regency. Using descriptive quantitative with a population of mothers under five, the sample used by some mothers of children under five at Posyandu Melati, Gendingan Village, Ngawi Regency who met the inclusion criteria were calculated using the Slovin formula totaling 46 people. The sampling used was purposive sampling with the research design used cross sectional, the process of collecting data by questionnaire. Mothers of toddlers who had a good level of knowledge in the Jasmine Posyandu in Gendingan Village, Ngawi Regency were 37 respondents (80.4%) while the development of toddlers in the Jasmine Posyandu in Gendingan Village, Ngawi Regency had the appropriate development of 40 children (87.0%). Spearman test results P value 0.000. The correlation value is 0.646, the level of strength of the relationship between the variables is strong. Positive coefficient, which means that the two variables are unidirectional. H0 is rejected and H1 is accepted, meaning that there is a relationship between the mother's level of knowledge about developmental stimulation and the development of toddlers at the jasmine posyandu, Gendingan Village, Ngawi Regency. Keywords:Mother's Knowledge, Developmental Stimulation, Toddler Development.  ABSTRAK Pengetahuan Ibu yang baik tentang stimulasi perkembangan akan berpengaruh pada perkembangan balita. Ibu berpengetahuan baik mengenai stimulasi perkembangan maka balitanya akan memiliki perkembangan sesuai dan optimal. Menganalisis adanya hubungan tingkat pengetahuan ibu tentang stimulasi perkembangan dengan perkembangan balita di posyandu melati Desa Gendingan Kabupaten Ngawi. menggunakan kuantitatif deskriptif dengan populasi ibu balita, sampel yang digunakan sebagian ibu balita di Posyandu Melati Desa Gendingan Kabupaten Ngawi yang memenuhi kriteria inklusi dihitung menggunakan rumus Slovin berjumlah 46 orang. sampling yang digunakan purposive sampling dengan desain penelitian yang digunakan cross sectional, proses pengumpulan data dengan kuesioner. Ibu balita yang memiliki tingkat pengetahuan baik di posyandu melati Desa Gendingan Kabupaten Ngawi sebesar 37 responden (80,4%) sedangkan perkembangan balita di Posyandu melati Desa Gendingan Kabupaten Ngawi memiliki perkembangan yang sesuai 40 anak (87,0%). Hasil uji spearman nilai P value 0,000. Nilai  korelasi 0,646, tingkat kekuatan hubungan antara variabel kuat. Koefisien positif yang berarti kedua variabel bersifat searah. H0 ditolak dan H1 diterima artinya ada hubungan antara tingkatan pengetahuan ibu tentang stimulasi perkembangan dengan perkembangan balita di posyandu melati Desa Gendingan Kabupaten Ngawi Kata Kunci: Pengetahuan Ibu, Stimulasi Perkembangan, Perkembangan Balita